Current awareness and attitude toward fertility preservation in Indonesia: A nationwide survey among health-care providers - Sarrah Ayuandari; Nurida Khasanah; Ismi W Riyanti; Agung Dewanto; Diannisa Ikarumi Enisar Sangun; Budi Wiweko (Wolters Kluwer Medknow Publications, 2021)
Context: Fertility preservation (FP) is necessary for cancer patients who develop infertility due to chemotherapy and radiotherapy. In Indonesia, many systematic steps and long-term continued actions must be taken to establish FP units since there has been an increasing incidence of cancer among people under 45 years old. Aims: This study aimed at a comprehensive evaluation on the awareness and practices of health-care providers (HCPs) toward FP. Settings and Design: This was a descriptive cross-sectional study. Subjects and Methods: A validated nationwide online survey was completed by 160 HCPs as a representative sample from 11 provinces in 2017 that provide medical care to cancer patients at hospitals or clinics. Statistical Analysis Used: Descriptive statistics, analysis of variance, logistic regression, and Pearson correlation tests were used for the statistical analysis. Results: Respondents were specialists (59.4%) and other HCPs (40.6%). Around 60% of the HCPs who performed cancer therapies already discussed the fertility issues with their patients. Meanwhile, the HCPs (60.7%) also tended not to consult and refer their patients to fertility experts (P < 0.05). However, those who discussed the risk of infertility with patients tended to consult with and refer them to a fertility consultant for further FP procedure as the follow-up for their discussions (odds ratio = 8.98, confidence interval 95%, P < 0.05). Conclusions: In Indonesia, FP awareness of the HCPs who performed cancer therapy was high. Nevertheless, attitudes to refer patients to fertility experts for possible FP management still need to be improved.